2013
DOI: 10.1111/1750-3841.12221
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Processing and Handling of Frozen Broccoli for Increased Sulforaphane Formation

Abstract: Frozen broccoli can provide a cheaper product, with a longer shelf life and less preparation time than fresh broccoli. We previously showed that several commercially available frozen broccoli products do not retain the ability to generate the cancer-preventative agent sulforaphane. We hypothesized that this was because the necessary hydrolyzing enzyme myrosinase was destroyed during blanching, as part of the processing that frozen broccoli undergoes. This study was carried out to determine a way to overcome lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Others have observed 7-to 12-fold increases in sulforaphane absorption when broccoli products or glucoraphanin are ingested in the presence of myrosinase activity [18][19][20][21][22]. All of these data confirm the importance of myrosinase activity for human absorption of sulforaphane from broccoli and broccoli products [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Others have observed 7-to 12-fold increases in sulforaphane absorption when broccoli products or glucoraphanin are ingested in the presence of myrosinase activity [18][19][20][21][22]. All of these data confirm the importance of myrosinase activity for human absorption of sulforaphane from broccoli and broccoli products [6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 59%
“…Myrosinase is activated by exposure to oxygen but is heat sensitive [10][11][12][13]. Blanching broccoli before freezing [6], or steaming [14] or cooking raw broccoli [15], reduces myrosinase activity and, in humans, decreases the net total bioavailability of sulforaphane from frozen broccoli by 90% [6,14,15].…”
mentioning
confidence: 99%
“…The anticarcinogenic benefits of sulforaphane, phenethyl isothiocyanate, and myrosinase-induced degradation products of indole glucosinolates can be maximized by raw consumption of the vegetables mentioned above or by the addition of functional myrosinase to denatured myrosinase (which results from cooking or blanching of frozen vegetables). 53 Comparison between isothiocyanate plasma concentrations from brassica vegetable ingestion and endogenous thiocyanate plasma concentrations…”
Section: Glucoraphanin Concentrations That Produce Beneficial Effectsmentioning
confidence: 99%
“…In recent studies, it was found that addition of an exogenous source of myrosinase (Daikon radish root and mustard seeds) to processed Brassica can reinitiate the hydrolysis of glucosinolates (Dosz & Jeffery, 2013;Ghawi, Methven, & Niranjan, 2013). Hence, evaluating other sources of myrosinase that are more stable under processing conditions is of importance.…”
Section: Introductionmentioning
confidence: 99%